Bioorthogonal Click and Release Reaction of Iminosydnones with Cycloalkynes. Issue 49 (10th November 2017) - Bernard, Sabrina; Audisio, Davide; Riomet, Margaux; Bregant, Sarah; Sallustrau, Antoine; Plougastel, Lucie; Decuypere, Elodie; Gabillet, Sandra; Kumar, Ramar Arun; Elyian, Jijy; Trinh, Minh Nguyet; Koniev, Oleksandr; et al.
Abstract: We report the discovery of a new bioorthogonal click‐and‐release reaction involving iminosydnones and strained alkynes. This transformation leads to two products resulting from the ligation and fragmentation of iminosydnones under physiological conditions. Optimized iminosydnones were successfully used to design innovative cleavable linkers for protein modification, thus opening up new areas in the fields of drug release and target‐fishing applications. This click‐and‐release technology offers the possibility of exchanging tags on proteins for functionalized cyclooctynes under mild and bioorthogonal conditions. Abstract : Click and cleave : Iminosydnones reacted smoothly with cycloalkynes under physiological, copper‐free conditions to form a click pyrazole product and release a urea product. Possible applications of this new reaction for drug release and protein trans‐tagging have been explored in proof‐of‐principle experiments.